O impacto das estratégias de marketing digital no branding: um estudo de caso do Bar Chico em Parintins/AM - Costa, Otávio da Rocha (Brasil, 2025)
This study aims to analyze, through a case study of “Bar Chico”, how digital marketing strategies contribute to the construction and strengthening of brand identity (branding) in the city of Parintins/AM. The methodology consisted of a mixed approach, involving the combination of quantitative and qualitative research designs. Due to the scope of the study, survey research and case study were also integrated. For data collection, a questionnaire with 19 questions was applied to Bar Chico's customers and a semi-structured interview with 14 questions regarding marketing and branding strategies. The results indicate that marketing strategies associated with branding build and strengthen the company's brand identity through content marketing, where the company sought to publicize the services offered and their attractions on digital platforms (Instagram, Facebook and WhatsApp) to attract its target audience and potential customers, Search Engine Optimization (SEO) through Google to optimize search engines, highlighting Bar Chico and Social Media Marketing, which creates content in an interactive and creative way to win over customers. Thus, it is concluded that marketing strategies have a great impact on the company's branding by establishing a satisfactory relationship with the customer, generating emotional connections with the brand and strengthening its identity in the market. This generates engagement and increased sales, in addition to contributing to customer loyalty and greater competitive advantages over the competition.